Costa Rica and the Brexit: Reflexions about social and economic posible effects - Rojas Noskova, Kira (2019)
The aims of this article is to generate a reflection about the effects on Costa Rica’s trade relations by the exit of the United Kingdom from the European Union. Complex interdependence theory and peripheral realism theory was adopted as theorical perspectives to understand this phenomenon. Besides, we offer a glance to the social derivations of this decision, which consequences can be studied from multiple angles. Methodologically, the literature review technique of primary and secondary sources is used. The findings it shows that trade between Costa Rica and the United Kingdom maintains a higher number of exports accountable to Costa Rica, and that this country should invest more effort to improve the exportable offer with products with greater added value. In conclusion, in the economic field, Brexit does not threaten the stability of the Costa Rican economy and beyond then, offers opportunities to strengthen relations between the two countries through the available commercial instruments and cooperation. In social sphere, it is a phenomenon that projects important lessons for the development of joint policies to improve integration processes.